Analisis Sistem Pengamanan Akses Autentikasi Jaringan dengan Metode Port Knocking dan Action Tarpit pada Router Mikrotik - Yefta Christian (Universitas Internasional Batam, 2019)
The use of mikrotik router in the process of forming a network system in a company both internally and externally is a common thing in the world of work, this is in line with the rapid development of technology today. In this study, researchers designed user permissions on ports using mikrotik routers as well as testing the security of port knocking methods and action tarpit firewalls. Port knocking method is a technique that temporarily closed port access. With the method of port knocking researchers can test the security of a port using a knocking port on the router mikrotik, so it can be known how safe port knocking method to protect certain ports. Port knocking used in mikrotik this router using winbox to see it, and also by using web service on winbox webfig already provided by party mikrotik router.